2013
DOI: 10.1080/13668803.2013.850402
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a thriving childcare workforce: a theory-driven qualitative analysis

Abstract: Following a positive organizational framework, this study fills a gap in the human service literature by examining what works to boost childcare workers' ability to thrive in their jobs. Drawing from Spreitzer, Sutcliffe, Dutton, Sonenshein, and Grant's model of thriving at work, this study examines effective mechanisms (affirming work conditions, cultivated job resources, and work engagement) that facilitate positive experiences at work for childcare providers. Qualitative data was collected from seven focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Paterson et al (2014) found heedful relating and task focus to mediate the effects of supervisor support and psychological capital on thriving. In caregiving occupations (e.g., nursing and childcare), relational resources such as trust and respect (Silen et al, 2019;Travis et al, 2014) promote thriving via supporting caregivers' agency in tailoring treatments to patients' specific needs (Vassbø et al, 2019). Individuals who lack personal resources that support agentic behaviors (e.g., self-efficacy; Novaes et al, 2020) may especially benefit from a supportive and thrivingenabling work environment.…”
Section: Antecedentsmentioning
confidence: 99%
“…Likewise, Paterson et al (2014) found heedful relating and task focus to mediate the effects of supervisor support and psychological capital on thriving. In caregiving occupations (e.g., nursing and childcare), relational resources such as trust and respect (Silen et al, 2019;Travis et al, 2014) promote thriving via supporting caregivers' agency in tailoring treatments to patients' specific needs (Vassbø et al, 2019). Individuals who lack personal resources that support agentic behaviors (e.g., self-efficacy; Novaes et al, 2020) may especially benefit from a supportive and thrivingenabling work environment.…”
Section: Antecedentsmentioning
confidence: 99%